A novel UV-curing liner for NEPE propellant: Insight from molecular simulations. (15th August 2020) - Zhang, Pingan; Yuan, Jianmin; Pang, Aimin; Tang, Gen; Deng, Jianru
Abstract: In this paper, a new simulation strategy was proposed for constructing the UV-curing crosslinking model by using computational programming. Based on this algorithm, the UV curing model of polyurethane acrylate (PUA) liner was effectively built at a molecular scale. Molecular dynamics (MD) simulations were first conducted to estimate the mechanical properties and thermal transition behavior, and the simulated results were a good agreement with the experimentally measured values. Then, the solubility parameters and radial distribution function (RDF) were calculated to get an in-depth understanding of the interface interaction between the liner and other components. Finally, we calculated the diffusion coefficient of nitrate plasticizer molecules in the liner and explored the influencing factors. The dynamic behavior of the nitrate plasticizer in the liner interface was also investigated, and the results demonstrated that PUA liner could effectively prevent the migration of plasticizer because of the higher crosslink density. These researches help us deeply understand the structure-property correlation and provide molecular insight into the mechanisms of nitrate plasticizer migration, which was useful for the structure design and material selection of NEPE propellant liner. Graphical abstract: Image 1 Highlights: A computational simulation model of UV curing network based on a simplified stochastic approach is proposed. The migration dynamic behavior of nitrate plasticizer molecules can be clearly observed by the multiscale simulation method. The PUA liner could effectively prevent the migration of plasticizer because of the higher crosslink density. MD simulation provides an effective method for exploring the structure-property relationship of cross-linked materials.